PERSPECTIVES IN ENGLISH LANGUAGE LEARNING: FIRST LANGUAGE SITUATION, SECOND LANGUAGE SITUATION AND FOREIGN LANGUAGE SITUATION - Santi Andriyani (Abjadia, 2016)
There are so many questions come to mind in relation to language learning. One of which is the ways in teaching and learning the language especially in formal education. This issue has been discussed since 1980s until now. Linguists who get involved in education field have done research in this field. They found that the main concentration in language teaching is the selection of approach based on the system governed the learners. Some perspectives appear in the language learning. The methods, approach, and principles which come and arise in the language learning are discussed. These terms influence the learning of English as a first language, second language or foreign language. English as a first language will be taught differently. It also happens to the learning of English as second and foreign language. It is because of different purpose in learning the language. In this article, the writer discuss some perspectives in language learning in first language situation, second language situation and foreign language situation.هناك كثير من الأسئلة تتبادر إلى الذهن فيما يتعلق بتعليم اللغة. واحدة منها هي الطرق في تعليم وتعلم اللغة وخاصة في التعليم الرسمي. وقد نوقشت هذه المسألة منذ 1980 (ثمانين) حتى الآن. وكان اللغويون يتورطون في مجال التعليم وإجراء الأبحاث في هذا المجال. ووجد الباحثون أن تركيز الرئيسي في تدريس اللغة هو اختيار النهج القائم على نظام محكوم المتعلمين. ويبدو أن بعض وجهات النظر في تعلم اللغة. وتناقش الطرق، والنهج والمبادئ التي تأتي وتنشأ في تعلم اللغة. هذه الشروط تؤثر على تعلم اللغة الإنجليزية كلغة أولى، لغة ثانية أو لغة أجنبية. اللغة الإنجليزية كلغة أولى وسيتم تدريسها بشكل مختلف. ويحدث أيضا في تعلم اللغة الإنجليزية كلغة ثانية والأجنبية. فذلك الاختلاف لأجل أغراض مختلفة في تعلم اللغة. وفي هذه المقالة، قامت الكاتبة بمناقشة بعض وجهات النظر في تعلم اللغة في وضع اللغة الأولى، واللغة الثانية واللغة الأجنبية